Walter Pater et la vieillesse : humanité et esthétique de la culture - Martine Lambert-Charbonnier (Cahiers Victoriens et Edouardiens)
Old age in Walter Pater's works is the time when the individual has the opportunity to think thoroughly upon life and culture. The feeling of growing old may first engender melancholy and bitterness as one considers all those lost days of youth. However, Pater's characters generally take the opportunity to start again and fulfill their quest of wisdom. Old people are more sympathetic with the sorrows of humankind. Looking back upon their own past, they remember their childhood and their first experiences and reflect on their own identity, on the human condition and on culture. Ageing is also an essential element in the arts, especially in architecture as buildings mature and ripen in the course of years and centuries. Old worn stones, old aesthetic forms are for future generations witnesses of immemorial times, allowing Pater's nineteenth-century arts critic to spiritually restore the past and contribute to the development of culture thoughout the ages.